Titanium wire implants with nanotube arrays: A study model for localized cancer treatment. (September 2016) - Kaur, Gagandeep; Willsmore, Tamsyn; Gulati, Karan; Zinonos, Irene; Wang, Ye; Kurian, Mima; Hay, Shelley; Losic, Dusan; Evdokiou, Andreas
Abstract: Adverse complications associated with systemic administration of anti-cancer drugs are a major problem in cancer therapy in current clinical practice. To increase effectiveness and reduce side effects, localized drug delivery to tumour sites requiring therapy is essential. Direct delivery of potent anti-cancer drugs locally to the cancer site based on nanotechnology has been recognised as a promising alternative approach. Previously, we reported the design and fabrication of nano-engineered 3D titanium wire based implants with titania (TiO2 ) nanotube arrays (Ti-TNTs) for applications such as bone integration by using in-vitro culture systems. The aim of present study is to demonstrate the feasibility of using such Ti-TNTs loaded with anti-cancer agent for localized cancer therapy using pre-clinical cancer models and to test local drug delivery efficiency and anti-tumour efficacy within the tumour environment. TNF-related apoptosis-inducing ligand (TRAIL) which has proven anti-cancer properties was selected as the model drug for therapeutic delivery by Ti-TNTs. Our in-vitro 2D and 3D cell culture studies demonstrated a significant decrease in breast cancer cell viability upon incubation with TRAIL loaded Ti-TNT implants (TRAIL-TNTs). Subcutaneous tumour xenografts were established to test TRAIL-TNTs implant performance in the tumour environment by monitoring the changes in tumour burden over a selected time course. TRAIL-TNTs showed a significant regression in tumour burden within the first three days of implant insertion at the tumour site. Based on current experimental findings these Ti-TNTs wire implants have shown promising capacity to load and deliver anti-cancer agents maintaining their efficacy for cancer treatment.